Model Pendugaan Biomassa Vegetasi Mangrove di Kabupaten Indragiri Hilir Riau - Endang Hilmi; Asrul Sahri Siregar (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
Indragiri Hilir mangrove forest is a type of one which is influenced by sea water tide, freshwater, soil texture, and salinity. The diversity of flora and fauna in the mangrove forest is relatively higher than that of many others in Indonesia. The potential vegetation is dominated by Bruguiera spp., Rhizophora spp., Avicennia spp., and Soneratia spp. This study was aimed to (1) determine biomass potential in Indragiri Hilir mangrove forest and (2) develop estimation model on the mangrove biomass with diameter of stem. The results showed that biomass potential of Rhizophora apiculata was 536.4 to 2,333.0 kg/tree, R. mucronata was 376.0 to 900.5 kg/tree, and Bruguiera spp. was 328.0 to 546.0 kg/tres. Estimation model on biomass of Bruguiera were 0.9450903501 D1.865827743 for stem biomass and 10.11259103 D 1.30096243 for total biomass, while those of R. apiculata were 0.2109981916 D 2.453342882 for stem biomass and 0.7574460068 D 2.232516567 for total biomass.